2004
DOI: 10.1524/ract.92.4.271.35612
|View full text |Cite
|
Sign up to set email alerts
|

Neutral oxorhenium(V) and oxotechnetium(V) complexes with novel amide thioether dithiolate ligands derived from cysteine

Abstract: Oxo complexes / Rhenium and technetium complexes / Thioether/amide ligand / Crystal structuresSummary. Bifunctional ligands able to form neutral complexes with radioactive technetium and rhenium and to couple to biological relevant anchor groups play an important role in the design of new radiopharmaceuticals for diagnosis and therapy. A novel tetradentate amide thioether dithiolate ligand HS−CH 2 CH 2 −S−CH 2 CONH−CH(COOR)CH 2 SH (H 3 SNSS) with R = CH 3 , C 10 H 21 was synthesized that forms stable complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The electronic structure of the center {VOS 4 } in [VO(bdt) 2 ] 2À (bdt 2À = 1,2-benzenedithiolato) has been studied by Cooney et al [14], providing valuable background information regarding the mode-of-action of vanadium-containing nitrate reductase (V-NR), analogous to molybdenum-containing bacterial NR. Oxocomplexes of rhenium(V) containing dithiolato ligands have been attracted attention due to their role in oxygen atom transfer reactions (OAT) [15][16][17], and because the nuclear properties of 186 Re and 188 Re, as a potential radiopharmaceuticals, not only for diagnosis but also for therapeutic purposes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure of the center {VOS 4 } in [VO(bdt) 2 ] 2À (bdt 2À = 1,2-benzenedithiolato) has been studied by Cooney et al [14], providing valuable background information regarding the mode-of-action of vanadium-containing nitrate reductase (V-NR), analogous to molybdenum-containing bacterial NR. Oxocomplexes of rhenium(V) containing dithiolato ligands have been attracted attention due to their role in oxygen atom transfer reactions (OAT) [15][16][17], and because the nuclear properties of 186 Re and 188 Re, as a potential radiopharmaceuticals, not only for diagnosis but also for therapeutic purposes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…48−51 In addition, it has been reported that 99g Tc complexes and their Re surrogates with almost identical crystal structures can exhibit different elution behavior. 52,53 Although the mechanism behind this observation remains unclear, the substitution inertness of Re complexes compared to 99g/99m Tc complexes is believed to play an important role. 52 Because a 0.4 to 1.1 min difference in retention times between the corresponding 99m Tc-and Re-SDPhe-TATE isomers was observed, we are unable to conclude whether 99m Tc is coordinated to SDPhe-TATE identically to Re, based on the current experimental data.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Characterization of 99m Tc complexes is often accomplished by chromatographic correlation with the corresponding Re complexes. , Although in some cases coelution was observed upon HPLC analysis, ,, in other cases the retention times of the 99m Tc complexes were found to differ by approximately half a minute to 2 min, which has not always been noted in the literature. In addition, it has been reported that 99g Tc complexes and their Re surrogates with almost identical crystal structures can exhibit different elution behavior. , Although the mechanism behind this observation remains unclear, the substitution inertness of Re complexes compared to 99 g /99m Tc complexes is believed to play an important role . Because a 0.4 to 1.1 min difference in retention times between the corresponding 99m Tc- and Re-SDPhe-TATE isomers was observed, we are unable to conclude whether 99m Tc is coordinated to SDPhe-TATE identically to Re, based on the current experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…The radiochemical purity of 123 I produced by the proton irradiation of 124 Xe has been shown to be an order of magnitude better 182 than that produced by similar irradiation of natural iodine, in the former case the level of 125 I contamination is about 0.01%.…”
Section: I]mentioning
confidence: 93%
“…For example, the proposed central nervous system imaging agents often utilized piperizine derivatives and thiols, 120,121 thiocresols 122 or related molecules. Similar ligands have been used in making new complexes based on oxy-technetium(V) which can then be used to label derivatives of cysteine 123 or serotonin 5-HT1A brain receptors. 124,125 Following the '3 + 1' idea many new technetium complexes have been based 126 on the hydrated tricarbonyl fragment.…”
Section: Technetium [ 99m Tc]mentioning
confidence: 99%